Pengaruh Kondisi Infrastruktur terhadap Pertumbuhan Ekonomi di Jawa Barat - Maqin, Abdul (Jurnal Trikonomika, 2011)
This study aims to obtain the empirical evidence on (1) Infrastructure condition of the road, education, health, and electricity in West Java, (2) the influence Infrastructure condition of the road, education, health, and electricity, labour and government expenditure to West Javaâs province economic growth.This study is characterized by descriptive as well as verificative research of which the study aims at giving picture and finding verification or reviewing and testing the existence of empirical theory of variables relationship which are formulated in the economic growth model. Model of data analysis used in this research to identify relationships between variables is Pooled Data Analyses. The research uses regression to measure fixed effect compassing of 22 cities and regencies in West Java.The research indicate that (1) The infrastructure condition of the road, education, and health are getting worst, nevertheless the electricity infrastructur is better than before in West Java, (2) Electricity infrastructure, labour and development expenditure have positive and significant influence on the economic growth. It means if the previous three variables increase, then economic growth will augment as well and vice versa. Road and education infrastructures have positive influence but not have significant on the economic growth. On the other hand, health infrastructure has negative correlation and not have significant influence on the economic growth.